Analysis of hundreds of cis-regulatory landscapes at high resolution in a single, high-throughput experiment - Hughes, J; Roberts, N; McGowan, S; Hay, D; Giannoulatou, E; Lynch, M; De Gobbi, M; Taylor, S; Gibbons, R; Higgs, D (Nature Publishing Group, 2014)
Gene expression during development and differentiation is regulated in a cell- and stage-specific manner by complex networks of intergenic and intragenic cis-regulatory elements whose numbers and representation in the genome far exceed those of structural genes. Using chromosome conformation capture, it is now possible to analyze in detail the interaction between enhancers, silencers, boundary elements and promoters at individual loci, but these techniques are not readily scalable. Here we present a high-throughput approach (Capture-C) to analyze cis interactions, interrogating hundreds of specific interactions at high resolution in a single experiment. We show how this approach will facilitate detailed, genome-wide analysis to elucidate the general principles by which cis-acting sequences control gene expression. In addition, we show how Capture-C will expedite identification of the target genes and functional effects of SNPs that are associated with complex diseases, which most frequently lie in intergenic cis-acting regulatory elements.